Low dose tadalafil effect on anthropometric and metabolic parameters in Iraqi diabetic obese men - Khazaal, Faris A. (AL-Kindy College Medical Journal, 2014)
Background: Phosphodiesterase-5 (PDE-5) inhibitorsrestore nitric oxide (NO) signaling and may reducecirculating inflammatory markers, and improve metabolicparameters through a number of mechanisms. Dailyadministration of the PDE-5 inhibitor, tadalafil (TAD) mayattenuate inflammation; improve fasting plasma glucose andtriglyceride levels and body weight. This study aims toevaluate the efficacy of low dose PDE-5 inhibitor, tadalafil(TAD) in controlling dysglycemia and body weight in obesediabetic men.Methods: Forty obese men with type 2 diabetes aged 30-50years incorporated in this study, all with A1c of 7-8.5%,attending obesity unit in AL-Kindy college of medicine.Weight, height, BMI, FPG, A1c, cholesterol, TG, HDL andLDL measured for all and advised for low calories diet andincreasing exercise and randomized into 2 groups , first(control) without and the second (therapy) with addition oftadalafil 2.5mg/day for 8 weeks, then remeasure all theparameters after. Results blotted in tables and statisticalanalysis done using SPSS program and t-test.Results: There was significant reduction in weight, BMI,FPG, cholesterol, TG and LDL, while no significant change in A1c , and although there was elevation in HDL but was insignificant in control group. In therapy group both weight, BMI, FPG, A1c, cholesterol, TG, and LDL show significant reduction, with mild insignificant elevation in HD. When compare the results of both groups significant results appear in percentage of change of FPG and A1c in therapy group.Conclusion: Low calories diet and exercise are effective inreducing obesity parameters in type 2 diabetes, in addition,improve dysglycemia and dyslipidemia , adding tadalafil2.5mg/day can add beneficial effect specifically for FPG andA1c significantly.